Tradisi “Nambut Panganten” dalam Perkawinan Adat Sunda dalam Pandangan Hukum Islam: Studi Kasus Desa Sembawa Kuningan Jawa Barat - Endang Mukhlis Hidayat (El 'Ailaah, 2023)
Nambut panganten is a tradition in traditional marriages that occur in the community where the reception or wedding invitation is held at the prospective groom first. Meanwhile, in practice, the bride-to-be is borrowed to be presented and sits side by side in the aisle with the groom-to-be at the reception which is held one day before the wedding contract. The fact is that in the teachings of Islam it is not accordance with the shari’a because they are not yet legally husband and wife. The purpose of the problem in this study is to find out how the prictice of the Nambut Panganten tradition is in Sembawa village, Kuningan West Java and to examine how Islamic law views the Nambut Panganten tradition in Sembawa village, Kuningan West Java. This study uses qualitative research methods. The type of this research and data collection techniques using interviews and documentation. The results of the study show that the practice of Nambut Panganten in Sembawa village, Kuningan West Java, when viewed from Islamic law, is not permissible because it is against the shari’a which contains elements of ikhtilat and khalwat.